2016
DOI: 10.3329/bmj.v44i2.27245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total abdominal hysterectomy over the decade in Holy Family Red Crescent Medical College Hospital - A retrospective observational study

Abstract: Hysterectomy is the commonest major surgical procedure in Gynaecology & usually performed to improve quality of life rather than to cure life-threatening conditions. The rates differ between countries depending on differences in morbidity, health economical aspects, traditions and attitudes. This retrospective observational study was carried out from 2001-2010 & included all cases of abdominal hysterectomy done for benign and non emergency conditions in the department of Obstetrics & Gynaecology, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only a few studies have compared pre-operative clinical diagnosis with histopathology of hysterectomy specimens. 19,20 In our study, the fibroid was the most common indication for hysterectomy. We had a preoperative indication of fibroid in 76 cases, but it was confirmed in 78 cases.…”
Section: Discussionmentioning
confidence: 67%
“…Only a few studies have compared pre-operative clinical diagnosis with histopathology of hysterectomy specimens. 19,20 In our study, the fibroid was the most common indication for hysterectomy. We had a preoperative indication of fibroid in 76 cases, but it was confirmed in 78 cases.…”
Section: Discussionmentioning
confidence: 67%
“…21 The highest proportion of patients (49.0%) of this study was in the 41-50 years of age group which was consistent with the findings of several other Bangladeshi studies and studies done abroad. In studies by Hossain et al 22 , and Nazneen et al 23 , majority of patients undergoing total abdominal hysterectomy was found to be in the age group of 41-50 years. Subrata et al 21 and Raza et al 24 reported that the highest percentage of patients was among 40-49 years.…”
Section: Table Viii: Year Wise Management Of Ovaries and Fallopian Tu...mentioning
confidence: 94%
“…Both the conditions were mostly found in the 41-50 year age group (18.82% and 15.29%). In another Bangladeshi study, Nazneen et al 23 reported that most of the abdominal hysterectomies were due to leiomyoma (46%) and done during 3rd and 4th decade. It was followed by abnormal uterine bleeding due to ovarian dysfunction (AUB-O), pelvic inflammatory disease (PID) and adenomyosis, all of which were among 41-50 year age group.…”
Section: Table Viii: Year Wise Management Of Ovaries and Fallopian Tu...mentioning
confidence: 99%